An Empirical Study of Bank Efficiency in South Africa Using the Standard and Alternative Approaches to Data Envelopment Analysis (DEA) - Erasmus, Coert (Journal of Economics and Behavioral Studies, 2014)
The paper investigates the efficiency of the major banks of South Africa using the standard and alternative approaches to Data Envelopment Analysis (DEA). The standard DEA approach measures efficiency utilising linear averages of outputs and inputs while the alternative DEA approach utilises nonlinear averages. Individual bank efficiency scores are estimated over the period 2006 to 2012, a period that allows analysis of the efficiency of the banks during the global financial crisis of 2008 to 2009. Under both approaches the majority of the major South African banks were observed to be DEA efficient, with the alternative approach improving the efficiency scores of those banks that were DEA inefficient under the standard approach. The global financial crisis did not affect the efficiency of the majority of the banks. Since the banks were DEA efficient prior the crisis, it could be argued that their efficiency was one of the contributory factors for their resilience during the global financial crisis.